2003
DOI: 10.1002/j.1681-4835.2003.tb00069.x
|View full text |Cite
|
Sign up to set email alerts
|

E‐Finance for Development: Global Trends, National Experience and SMEs

Abstract: IntroductionThe title of this chapter accurately reflects its content: it covers current developments in efinance with the initial emphasis being on overall global trends. The second half of the chapter is an exploration of how these developments are likely to impact SMEs in developing countries in the near future. There is a thorough coverage of relevant e-finance topics including: Internet banking; Internet payments; international electronic trade and finance systems; online credit information and credit ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In the era of information and communication technology, sunk costs are becoming less important partly because electronic delivery modes do not rely on branch networks (Claessens et al , 2002). Purcell and Toland (2003) state that banks and other agencies maintain credit information databases, which hold information on the financial performance of different companies and businesses. Companies in the developing countries, Serasa (www.serasa.com.br/ingles/i‐index.htm) in Brazil for instance, provides the largest credit information databank on institutional and household borrowers in Latin America and all of its products and reports are available online.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of information and communication technology, sunk costs are becoming less important partly because electronic delivery modes do not rely on branch networks (Claessens et al , 2002). Purcell and Toland (2003) state that banks and other agencies maintain credit information databases, which hold information on the financial performance of different companies and businesses. Companies in the developing countries, Serasa (www.serasa.com.br/ingles/i‐index.htm) in Brazil for instance, provides the largest credit information databank on institutional and household borrowers in Latin America and all of its products and reports are available online.…”
Section: Introductionmentioning
confidence: 99%
“…The security risks are higher for this channel. Usually the implementation of Internet banking requires substantial investment from a bank, as well as a major restructuring of its internal information flows and procedures (Efinance, 2001b(Efinance, , 2003bPurcell & Toland, 2003). A simpler version of Internet banking services has been introduced by a few banks: Using only the e-mail facility, the client can obtain information or request simple transactions from its bank (e.g., Piraeus Bank).…”
Section: The Channel Portfolio Of Romanian Banksmentioning
confidence: 99%
“…11 (4) 343-362 (2005 Finance and banking are information-intensive industries, which can be positively transformed by the development of ICT. However, a 1999 World Bank (Purcell & Toland, 2003) survey reported the average on-line banking penetration for developing countries to be only 5%. The main challenges encountered by developing countries in implementing multichannel banking activities are (Hadidi, 2003) • The ability to adopt global technology to the local requirements • The ability to strengthen the public support for e-finance • The ability to create the necessary level of regulatory and institutional frameworks • The ability to mainstream SMEs toward e-finance.…”
Section: Introduction: Ict and Developmentmentioning
confidence: 96%
“…In this respect, Allen et al [ 10 ] and Domowitz [ 11 ] argued that electronic finance technology overcomes information asymmetries between customers and producers and costs associated with data handling. Purcell and Toland [ 12 ] suggested that ICT plays a greater role in managing credit information data records and delivering debtors and institutional references. Shamim [ 13 ] and Majeed and Ayub [ 14 ] exhibited that ICT can support economic growth by decreasing operational and informational expenses.…”
Section: Introductionmentioning
confidence: 99%